2021
DOI: 10.1155/2021/6623045
|View full text |Cite
|
Sign up to set email alerts
|

Sialolipoma of the Floor of the Mouth with Immunohistological Analysis

Abstract: Lipomas are relatively rare in the head and neck, and sialolipoma was described as an entity about 20 years ago as lipoma that entraps salivary gland tissue. Less than 10 cases have been described in the floor of the mouth not related to the major salivary glands. Here, we report a case of sialolipoma affecting the floor of the mouth in a 47-year-old patient and reviewed the clinical, histologic, and immunohistochemical characteristics of the lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Zahrani et al described a case of a 47-year-old male with a swelling of the floor of the mouth (3.5 × 4.7 × 1.5 cm in its greatest dimension), excised through an intraoral approach, with a definitive histological diagnosis of sialolipoma. 10 K. Gibson et al described another similar clinical case; they reported a case of a large lipoma of the mouth floor (8.5 × 4.0 × 1.0 cm), excised with neuromonitoring of the right hypoglossal nerve, with a definitive histological diagnosis of simple lipoma without invasion of the surrounding tissues; no focal cartilage metaplasia was described. 4 Differential diagnoses are very important and physician should base their considerations on patients' history and physical examination, imaging, and pathological findings.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zahrani et al described a case of a 47-year-old male with a swelling of the floor of the mouth (3.5 × 4.7 × 1.5 cm in its greatest dimension), excised through an intraoral approach, with a definitive histological diagnosis of sialolipoma. 10 K. Gibson et al described another similar clinical case; they reported a case of a large lipoma of the mouth floor (8.5 × 4.0 × 1.0 cm), excised with neuromonitoring of the right hypoglossal nerve, with a definitive histological diagnosis of simple lipoma without invasion of the surrounding tissues; no focal cartilage metaplasia was described. 4 Differential diagnoses are very important and physician should base their considerations on patients' history and physical examination, imaging, and pathological findings.…”
Section: Discussionmentioning
confidence: 97%
“…A. Zahrani et al described a case of a 47-year-old male with a swelling of the floor of the mouth (3.5 × 4.7 × 1.5 cm in its greatest dimension), excised through an intraoral approach, with a definitive histological diagnosis of sialolipoma 10 …”
Section: Discussionmentioning
confidence: 99%
“…Such cases manifested clinically as submucosal, wellcircumscribed nodules with a soft to firm consistency, normal to yellowish [5]. The lesion is well-circumscribed on gross examination, and it has a uniform yellowish color, a soft to firm consistency, and a smooth or irregular surface.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mature adipocytes and normal salivary gland tissue represents this tumor. Clinically, this type of lipoma typically manifests as an asymptomatic, slow-growing, soft, movable tumor with no evidence of mucosal or skin abnormalities or other disorders of the salivary glands [5]. Lipomas may have a wide range of radiographical features on the CT and MRI and are useful to assess the extension and location of the lesion.…”
Section: Introductionmentioning
confidence: 99%